A Multispectral Single‐Layer Frequency Selective Surface Absorber for Infrared and Millimeter Wave Selective Bi‐Stealth. Issue 6 (30th January 2022) - Shim, Hyeon Bo; Han, Kiwook; Song, Jookwon; Hahn, Jae W.
Abstract: The multispectral electromagnetic (EM) absorber based on the frequency selective surface (FSS) has been applied with interest in the field of stealth technology due to its ability to avoid detectors or guided weapons at multiple wavelengths simultaneously. The multispectral absorption performance is generally accomplished by stacking different types of FSS absorbers in multiple layers. Herein, a thin and flexible multispectral single‐layer FSS (MSLF) absorber is presented using a micro‐holed, macroscale FSS combined with an infrared (IR) absorbing ground. The FSSs are simplified to MSLF by changing the absorbing layered microstructure to a transmitting microstructure. Dual‐band millimeter waves (MMWs) are absorbed by the macroscale resonance cavity, while the target IR waves are absorbed by the IR absorbing ground after penetrating the micro‐hole array pattern. Thermal emission is reduced significantly due to its low emissivity at IR bands other than the target IR. It is confirmed analytically and experimentally that patterns of various sizes do not exhibit functional crosstalk. The demonstrated multispectral absorption and low thermal emission make this a very promising material for IR−MMW selective bi‐stealth. Furthermore, the proposed structure can be applied to existing macroscale patterns in order to increase their applicability by providing additional selectivity without any functional interference. Abstract : A thin and flexible multispectral single‐layer frequency selective surface absorber is presented using a micro‐holed, macroscale frequency selective surface combined with an absorbing ground. Dual‐band millimeter waves (MMWs) and target near‐infrared (IR) signals are absorbed while the thermal emission is reduced significantly. The demonstrated multispectral absorption and low thermal emission make this a very promising material for IR−MMW selective bi‐stealth.